2007
DOI: 10.1007/s00216-007-1487-5
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-based label-free method for hemin recognition and DNA assay by capillary electrophoresis with chemiluminescence detection

Abstract: An aptamer-based label-free approach to hemin recognition and DNA assay using capillary electrophoresis with chemiluminescence detection is introduced here. Two guanine-rich DNA aptamers were used as the recognition element and target DNA, respectively. In the presence of potassium ions, the two aptamers folded into the G-quartet structures, binding hemin with high specificity and affinity. Based on the G-quartet-hemin interactions, the ligand molecule was specifically recognized with a Kd approximately 73 nM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…Literature analysis performed by us showed that different experimental conditions were used to determine CL activity of PMDNAzyme [22][23][24]28]. In turn, it does not allow fully using the catalytic potential of PMDNAzyme in analytical practice, where it is desirable to have a catalyst with the maximum possible activity.…”
mentioning
confidence: 99%
“…Literature analysis performed by us showed that different experimental conditions were used to determine CL activity of PMDNAzyme [22][23][24]28]. In turn, it does not allow fully using the catalytic potential of PMDNAzyme in analytical practice, where it is desirable to have a catalyst with the maximum possible activity.…”
mentioning
confidence: 99%
“…In addition to the ECL in visible region, the near-infrared ECL of metal nanoclusters was also obtained. Ding's group reported the near-infrared ECL of Au 25 (SC 2 H 4 Ph) 18 + -C 6 F 5 CO 2 − (Au 25 + ) (SC 2 H 4 Ph=2-phenylethanethiol) [65], Au 25 (SC 2 H 4 Ph) 18 − (Au 25 − ) [66], Au 144 (SC 2 H 4 Ph) 60 [67], Au 38 (SC 2 H 4 Ph) 24 [68], Au 25 (SC 2 H 4 Ph) 18 [69], successively.…”
Section: Chemical Reductive Synthesismentioning
confidence: 99%
“…It can be defined concisely as chemical reactions that emit light [16]. CL has been widely used as detection method in many fields because of its many advantages: large linear response, fast light emission, high stability of reaction reagents, low consumption of expensive reagents, cheap devices, and no problems about light scattering, source instability, or high background because of no excitation light source needed [17][18][19][20][21][22][23][24][25][26][27]. However, the CL emission of molecular systems is usually weak due to low quantum efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Detection as low as 0.01% of the minor enantiomer in a nonracemic mixture can be achieved, in a short analysis time (,5 min). Li et al [58] developed an aptamer-based assay to detect the haemin with chemiluminescence (CL) detection [58]. The protein behaved like a direct indicator for the moleculeaptamer interaction; when haemin was bound by aptamers and the complex was separated by CE, a decrease in the CL signal of free haemin occurred.…”
Section: Affinity Probe Ce (Apce)mentioning
confidence: 99%